Forgiveness In Early Adult Women With Divorce Parents - Dwi Melinda Wulandari; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2023)
This study aims to determine the description of forgiveness in early adult women with divorced parents and the factors that influence a person to do forgiveness. This research uses a qualitative approach with a case study method. Data obtained from semi-structured interviews with narrative analysis techniques. Participants in this study were early adult women who had experienced divorced parents when they were 6-12 years old. With reference to the two dimensions of forgiveness, namely the intrapsychic and interpersonal dimensions, this study shows that two participants have succeeded in doing forgiveness and one participant has not succeeded in doing forgiveness. For individuals who have successfully done forgiveness, it shows a positive change in their life and the relationship with their parents has returned to normal. For participants who have not succeeded in forgiving their parents, they are still filled with feelings of hatred, disappointment, anger, and heartache. Factors that influence such as relationship status as a family, religiosity, and the quality of interpersonal relationships. Meanwhile, inhibiting factors include focusing on parents' mistakes, feeling hurt, experiencing deep sadness, painful experiences, unfavorable social environment, avoidance behavior, and having poor judgment towards parents. Key word : Forgiveness, early adult women